In Search of the Nordic Working Life Model; Introduction to the Thematic Issue - Kasvio, Antti; Gonäs, Lena; Skorstad, Egil J. (Nordic Journal of Working Life Studies, 2012)
The theme of this issue is “in search of the Nordic working life model.” The main reason for choosing this theme is related to the widespread observation that several features of the Nordic institutions of work have been considered atypical when compared with those prevailing in other advanced industrial societies. We are not, of course, the first to make such an observation, and much effort has been spent in order to sort out what we actually talk about when we apply a term like the Nordic model. However, in spite of this effort, we are still toiling with the question of what it is that entitles us to talk about a specific order. Furthermore, if it really exists, will it be able to survive in the face of far-reaching changes that may be expected to take place in the coming decades? On what kinds of resources may it be based in the future? In the following, we will present some speculations upon such questions while distinguishing between qualities at the societal and organizational level. This may, of course, be considered an artificial differentiation since organizations are a part of society. Nonetheless, we choose to apply this distinction based on analytical reasons. In this way we hope to better illustrate how these entities are linked together in a mutual relationship, thus contributing both to stability and to change. At the end of the introduction, we will give a brief orientation of the content of this issue (...)